Status of the World’s Soil Resources Technical Summary - Alavipanah, Seyed Kazem (2015)
This document presents the first major global assessment ever on soils andrelated issues.Why was such an assessment not carried out before? We have taken soils for granted for a long time. Nevertheless, soils are the foundation of food production and food security, supplying plants with nutrients, water, and support for their roots. Soils function as Earth´s largest water filter and storage tank; they contain more carbon than all above-ground vegetation, hence regulating emissions of carbon dioxide and other greenhouse gases; and they host a tremendous diversity of organisms of key importance to ecosystem processes.However, we have been witnessing a reversal in attitudes, especially in light ofserious concerns expressed by soil practitioners in all regions about the severethreats to this natural resource. In this more auspicious context, when theinternational community is fully recognizing the need for concerted action , theIntergovernmental Technical Panel on Soils (ITPS), the main scientific advisorybody to the Global Soil Partnership (GSP) hosted by the Food and AgricultureOrganization of the United Nations (FAO), took the initiative to prepare thismuch needed assessment.The issuance of this first Status of the World?s Soil Resources report was most appropriately timed with the occasion of the International Year of Soils (2015) declared by the General Assembly of the United Nations. It was made possible by the commitment and contributions of hosts of reputed soil scientists and their institutions. Our gratitude goes to the Lead Authors, Contributing Authors, Editors and Reviewers who have participated in this effort, and in particular to the Chairperson of the ITPS, for his dedicated guidance and close follow up. Many governments have supported the participation of their resident scientists in the process and contributed resources, thus also assuring the participation of experts from developing countries and countries with economies in transition. In addition, a Technical Summary was acknowledged by representatives of governments assembled in the Plenary Assembly of the GSP, signaling their appreciation of the many potential uses of the underlying report. Even more comprehensive and inclusive arrangements will be sought in the preparations of further, updated versions.